Application of flood index in monitoring Flood-plain ecosystems (by the example of the Middle Ob flood-plain); Bulletin of the Tomsk Polytechnic University; Vol. 310, № 3 - Bolotnov V. P. (Earth science, 2007)
Заглавие с титульного листа